PRÁTICAS PEDAGÓGICAS COM CRIANÇAS COM TRANSTORNO DO ESPECTRO AUTISTA: Uma proposta de intervenção na Sala de Recursos Multifuncionais de uma creche-escola no município de São José de Ribamar – MA - MORAES, Louriane Lindoso (2024)
This dissertation aims to investigate the early intervention of pedagogical practices adopted by Multifunctional Resource Room teachers, and their implications in the educational area of children with Autism Spectrum Disorder (ASD), enrolled at the Municipal School of Early Childhood Education “Nova Terra”, for the preparation of a Methodological Guidelines Booklet. To achieve the proposed purpose, it was opted for a qualitative research approach, anchored in bibliographic and applied research. For bibliographical research, a survey of scientific productions on the topic in question was carried out, as well as an analysis of national and international documents in the area of special education. The applied research was carried out at the Municipal School of Early Childhood Education “Nova Terra”, located in the municipality of São José de Ribamar – MA. The research participants were the teacher specialized in Special Education, an Early Childhood Education teacher, a Day Care Assistant and a parent/guardian of the student with ASD enrolled and attending the regular classroom and the Multifunctional Resource Room (SRM). The following data collection instruments were used: documentary research, participant observation in the regular classroom and in the SRM, semi-structured interview with the Special Education specialist teacher, semi-structured questionnaires with the Early Childhood Education teacher, Daycare assistant and the person responsible for the student with ASD. Data analysis was carried out using Content Analysis (Bardin, 2011), and data interpretation was carried out through tables, charts and photographs. It was found that the specialist teacher in Special Education, the Early Childhood Education teacher and the Daycare assistant do not present a specific theoretical framework, but use, in their pedagogical practice, principles of Applied Behavior Analysis (ABA) and Treatment and Education for Autistic and Children with Communication-Related Disabilities (TEACH). The research also revealed that the teacher specialized in Special Education does not have the time to monitor the work of the teachers in the Regular Education classroom, which is why the guidelines are passed on to the morning shift teachers in person, and to the afternoon shift teachers virtually, through the WhatsApp application. In addition to this difficulty, the teacher specialized in Special Education also pointed out two more difficulties in relation to caring for students with ASD: the issue of organizing students' schedules and the quantity and type of SRM materials. Based on the research results, a Booklet of Methodological Guidelines was produced – Knowing to intervene – with the aim of helping teaching professionals and families, through information about ASD and interventions aimed at caring for children with ASD in the age group from two to five years. It is concluded that it is important to carry out studies addressing early interventions, based on scientific evidence, that can contribute to improving the quality of life, socialization and learning of children with ASD, and the need, on the part of public authorities, for programs for training teachers in early intervention with children with ASD.